Seeing people through : unleash your leadership potential with the process communication model - Regier, Nate (Berrett-Koehler Publishers, 2020)
"NASA, Pixar, and BMW all use the Process Communication Model as a way of training leaders to connect effortlessly with anyone. This book simplifies the complex model to make it easy for anyone to use"--